Tackling homophobia, biphobia and transphobia in football: what (if anything) works? - Crolley, Liz (Hate crime in football, 2023)
This chapter explores the different approaches taken in recent years to address homophobia, biphobia and transphobia in football and analyses their impact. It contextualizes the situation in football by looking at societal trends more broadly amid recent media coverage of hate crime targeting LGBT+ people. By examining case studies and interviewing key people involved in LGBT+ organizations in football and their allies, the chapter seeks to identify what makes LGBT+ campaigns successful and proposes recommendations for future engagement with fans and communications around hate crimes directed at LGBT+ people.